Understanding Sustainability: The Importance of Sustainable Development and Comprehensive Plans — Goals, Objectives, Policies - Jeffrey P. Gellermann; Mickie E. Swisher; Karla A. Lenfesty (EDIS)
FCS7242, a 4-page fact sheet by Jeffrey P. Gellerman, Mickie E. Swisher, and Karla A. Lenfesty, discusses the comprehensive plan, its components, and its role in sustainable community development. Published by the UF Department of Family Youth and Community Sciences, February 2010.